Concrete Ceramic Waste Slab (CCWS) - Mohd Mustafa, Al Bakri Abdullah; Kamarudin, Hussin; Che Mohd Ruzaidi, Ghazali; Shamsul Baharin, Jamaludin (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my